Non-coeliac gluten/wheat sensitivity: advances in knowledge and relevant questions. (2nd January 2017) - Volta, Umberto; Caio, Giacomo; Karunaratne, Tennekoon B.; Alaedini, Armin; De Giorgio, Roberto
ABSTRACT: Introduction : Non-coeliac gluten/wheat sensitivity (NCG/WS) is a syndrome characterized by intestinal and extra-intestinal symptoms occurring a few hours or days after the ingestion of gluten and wheat proteins in patients testing negative for coeliac disease and wheat allergy. Areas covered : The present review deals with recent scientific acquisitions of this gluten-related syndrome, including pathogenetic mechanisms, clinical picture, symptom score, biomarkers and double-blind placebo-controlled trial for diagnosis, and treatment. The methodology used was a literature search on NCG/WS using Medline and Premedline from 1970 to August 2016. Expert commentary : We discussed the pathogenesis of symptom generation and altered gut physiology in NCG/WS. Possible mechanisms include innate and adaptive immune activation, impaired intestinal epithelial barrier and changes in gut microbiome. These interlinked factors may be exploited for their clinical relevance as possible biomarkers. A systemic immune response to microbial and wheat antigens, together with intestinal cell damage, occurs in patients with NCG/WS. Due to the lack of established biomarkers, it is mandatory to validate the diagnosis of the syndrome by means of a well-defined work-up involving dietary challenge. Finally, dietary and other therapeutic indications have been thoroughly reviewed.